PENGARUH PERSEPSI MANFAAT, KEMUDAHAN PENGGUNAAN, DAN RISIKO TERHADAP MINAT MENGGUNAKAN QRIS PADA MASYARAKAT DI KOTA JAMBI - Muhklis Ananta Taryanda; Rofiqoh Ferawati; Beid Fitrianova Andriani (CV. KAMPUS AKADEMIK PUBLISING, 2024)
QRIS is a QR code-based payment standard set by Bank Indonesia to support and facilitate digital payments in Indonesia, as an effort to encourage the realization of an integrated payment system. The purpose of this study was to examine the effect of perceived benefits, ease of use, and risk on interest in using qris in the people of jambi city. The research method used is quantitative method. The population and samples used in this study were people in the city of Jambi. Data collection was carried out by distributing questionnaires with Likert scale measurements. Then, the data testing techniques used in this study are validity and reliability tests, R-Squer tests, and hypothesis testing through bootsrapping using Smart PLS 3.0 software. The results showed that perceived ease of use, and risk had a positive and significant effect on interest in using qris while perceived benefits had a positive and insignificant effect on purchasing decisions.